Significance of Climate Indices to Benthic Conditions Across the Northern North Atlantic and Adjacent Shelf Seas - Johnson, Clare; Inall, Mark; Gary, Stefan; Cunningham, Stuart (Frontiers in Marine Science, 2020)
The northern North Atlantic Ocean and its adjacent shelf seas, are influenced by several large-scale physical processes which can be described by various climate indices. Although the signal of these indices on the upper ocean has been investigated, the potential effects on vulnerable benthic ecosystems remains unknown. In this study, we examine the relationship between pertinent climate indices and bottom conditions across the northern North Atlantic region for the first time. Changes are assessed using a composite approach over a 50 year period. We use an objectively-analysed observational dataset to investigate changes in bottom salinity and potential temperature, and output from a high-resolution ocean model to examine changes in bottom kinetic energy. Statistically significant, and spatially coherent, changes in bottom potential temperature and salinity are seen for the North Atlantic Oscillation (NAO), Atlantic Meridional Overturning Circulation (AMOC), Atlantic Multi-decadal Oscillation (AMO) and Subpolar Gyre (SPG); with statistically significant changes in bottom kinetic energy seen in the subpolar boundary currents for the NAO and AMOC. As the climate indices have multi-annual timescales, changes in bottom conditions may persist for several years exposing sessile benthic ecosystems to sustained changes. Variations in baseline conditions will also alter the likelihood of extreme events such as marine heatwaves, and will modify any longer-term trends. A thorough understanding of natural variability and its effect on benthic conditions is thus essential for the evaluation of future scenarios and management frameworks.